Transcriptomics and Alternative Splicing Analyses Reveal Large Differences between Maize Lines B73 and Mo17 in Response to Aphid Rhopalosiphum padi Infestation - Song, Juan; Liu, Hui; Zhuang, Huifu; Zhao, Chunxia; Xu, Yuxing; Wu, Shibo; Qi, Jinfeng; Li, Jing; Hettenhausen, Christian; Wu, Jianqiang (Frontiers in Plant Science, 2017)
Maize (Zea mays L.) is a staple crop worldwide with extensive genetic variations. Various insects attack maize plants causing large yield loss. Here, we investigated the responses of maize B73, a susceptible line, and Mo17, a resistant line, to the aphid Rhopalosiphum padi on metabolite and transcriptome levels. R. padi feeding had no effect on the levels of the defensive metabolites benzoxazinoids (Bxs) in either line, and Mo17 contained substantially greater levels of Bxs than did B73. Profiling of the differentially expressed genes revealed that B73 and Mo17 responded to R. padi infestation specifically, and importantly, these two lines showed large gene expression differences even without R. padi herbivory. Correlation analysis identified four transcription factors (TFs) that might account for the high Bx levels in Mo17. Similarly, genome-wide alternative splicing (AS) analyses indicated that both B73 and Mo17 had temporally specific responses to R. padi infestation, and these two lines also exhibited large differences of AS regulation under normal condition, and 340 genes, including ten TFs, were constantly differentially spliced. This study provides large-scale resource datasets for further studies on the mechanisms underlying maize-aphid interactions, and highlights the phenotypic divergence in defense against aphids among maize varieties.